A compact city for the wealthy? Employment accessibility inequalities between occupational classes in the London metropolitan region 2011. (June 2020) - Smith, Duncan A.; Shen, Yao; Barros, Joana; Zhong, Chen; Batty, Mike; Giannotti, Mariana
Abstract: The prevalence of gentrification and housing marketisation processes in many cities points to increasingly wealthy inner-city areas and potentially greater population segregation by income. It is plausible that these trends are contributing to regional accessibility inequalities, though quantitative research testing this link is limited. This paper examines differences in employment accessibility between Standard Occupational Classification groups in the London Metropolitan Region for 2011 for car, transit, bus only and walking modes. Additionally, changes in occupational class populations 2006–2016 are considered, revealing continuing inner-city gentrification. Employment accessibility is calculated using cumulative measures, based on travel times from multi-modal network modelling. The results show that while car accessibility is relatively equal between occupational classes, public transport, bus and walk accessibility have significant inequalities favouring professional classes. Low income groups have lower accessibility for the most affordable bus and walk modes, and inequalities are greater for residents in the wider metropolitan region. Furthermore, professional groups combine accessibility advantages with the highest rates of owner occupation, maximising housing wealth benefits. Lower income groups are exposed to rent increases, though this is offset by social housing, which remains the most prevalent tenure in Inner London for low income classes.